Accuracy evaluation of position and speed control of Servo motor using PLC - Dwi Junita, Revidadina; Yuhendri, Muldi (Department of Electrical Engineering Universitas Negeri Padang, 2025)
The focus of this study is on the accuracy of the SIMOTICS S-1FL6 servo motor control, which is operated using a Siemens S7-1200 PLC and a Sinamics V90 VSD, with the help of a Human Machine Interface (HMI). This study quantitatively examines the motor speed in achieving the desired position (0°-360° unidirectional and clockwise) at 10 and 100 RPM, as well as the rotation accuracy at 10 to 100 RPM. The position accuracy evaluation results indicate that while the system provides good pressure at 10 RPM, the accuracy there is significant at 100 RPM, especially during complex operations. In addition, the overall accuracy of the rotation speed generally indicates the system's ability to achieve the RPM goal, even if there are occasional fluctuations in the Speed Error resulting in overshoot or undershoot. Thus, the results of this accuracy testing indicate that the developed control system successfully controls the SIMOTICS S-1FL6 servo motor in real-time, resulting in a high level of accuracy and is suitable for applications that monitor pressure from low to high as well as the rate of return from low to high